Chemically Modified Coconut Shell Biochar for Removal of Heavy Metals from Aqueous Solution - Muhammad, Imran-Shaukat; Nur Rafikah, Rosli; Rafeah, Wahi; Sharifah Mona, Abd Aziz Abdullah; Zainab, Ngaini (Trans Tech Publications Ltd, Switzerland, 2021)
In this study, coconut shells were converted into biochar via pyrolysis and chemically modified via an acid-base treatment to enrich its adsorption capabilities. Batch experiments were carried out to analyze the adsorption potential of the modified coconut shell (MCSC) for removal of chromium, nickel, and copper from aqueous solution. The chemical modification increased the surface area of MCSC to 185.712 m2 /g. Batch adsorption study using MCSC resulted in 99% removal of copper, 95% (nickel), and 39% (chromium). The adsorption of studied metal ions fitted well with Langmuir isotherm, showing a monolayer adsorption process. A kinetic analysis showed that all the samples match a strong correlation coefficient in pseudo-second-order (R2 >0.95), indicating the occurrence of a chemical adsorption process.